Grain size anlysis of composite sediment core NC_08/01 - Kasper, Thomas; Wang, Junbo; Schwalb, Antje; Daut, Gerhard; Plessen, Birgit; Zhu, Liping; Mäusbacher, Roland; Haberzettl, Torsten (In: Kasper, T et al. (2023): Sedimentological and geochemical analyses of composite sediment core NC_08/01 from lake Nam Co [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.961238, 2023)
Presented are analytical data from lacustrine sediment cores, retrieved from Lake Nam Co (Tibetan Plateau). The sediment core is a composite of one gravity core, taken with a Rumohr-Meischner gravity corer (63 mm diameter) and a piston core, retrieved using an uwitec piston coring system (http://www.uwitec.at; 90 mm diameter). The composite core labelled <NC 08/01> comprises a total length of 10.378 m. The cores were obtained at N 30.737417, E 090.790333 at a water depth of 93 m on 2008-09-15. The purpose of obtaining this sediment core was to establish a high-resolution record of climate (monsoonal) and environmental change using multiple proxy data. The dataset comprises analytical data based on sedimentological, inorganic geochemical, mineralogical and isotope-geochemical methods. Specifically: sediment water content & density; magnetic susceptibility; particel size data; quantitative inorganic geochemical data (ICP-OES aqua regia and HCL digestions); semi-quantitative XRF elemental data; carbon, nitrogen, sulfur contents; qualitative mineralogical data; bulk sediment stable carbon and oxygen isotope data.
Keywords: Asian Monsoon; lake sediment proxies; Nam Co